VEGF Mediates ApoE4-Induced Neovascularization and Synaptic Pathology in the Choroid and Retina - Antes, Ran; Salomon-Zimri, Shiran; C. Beck, Susanne; Garcia Garrido, Marina; Livnat, Tami; Maharshak, Idit; Kadar, Tamar; Seeliger, Mathias; Weinberger, Dov; M. Michaelson, Daniel (Current Alzheimer Research, 2015)
Apolipoprotein E4 (apoE4), the most prevalent genetic risk factor for Alzheimer's disease (AD), is associated with neuronal and vascular impairments. Recent findings suggest that retina of apoE4 mice have synaptic and functional impairments. We presently investigated the effects of apoE4 on retinal and choroidal vasculature and the possible role of VEGF in these effects. There were no histological differences between the retinal and choroidal vasculatures of naïve apoE3 and apoE4 mice. In contrast, laserdriven choroidal injury induced higher levels of choroidal neovascularization (CNV) in apoE4 than in apoE3 mice. These effects were associated with an inflammatory response and with activation of the Muller cells and asrocytic markers gluthatione synthetase and GFAP, all of which were more pronounced in the apoE4 mice. CNV also induced a transient increase in the levels of the synaptic markers synaptophysin and PSD95 which were however similar in the apoE4 and apoE3 naive mice. Retinal and choroidal VEGF and apoE levels were lower in naïve apoE4 than in corresponding apoE3 mice. In contrast, VEGF and apoE levels rose more pronouncedly following laser injury in the apoE4 than in apoE3 mice. Taken together, these findings suggest that the apoE4-induced retinal impairments, under basal conditions, may be related to reduced VEGF levels in the eyes of these mice. The hyper-neovascularization in the apoE4 mice might be driven by increased inflammation and the associated surge in VEGF following injury.
Keywords: neovascolarization